Evidence for more intensive cholesterol lowering. Issue 4 (August 2017) - Soran, Handrean; Kwok, See; Adam, Safwaan; Ho, Jan Hoong; Durrington, Paul N.
Abstract : Purpose of review: In randomized clinical trials, reduction in cardiovascular disease (CVD) risk with cholesterol-lowering drugs correlates with the LDL cholesterol decrease. However, because the majority have investigated a fixed statin dose, current guidelines disagree about the use of statin dose titration or non-statin adjunctive cholesterol-lowering drugs. Recent findings: We conducted a meta-analysis of all randomized controlled trials with CVD end-points, comparing two intensities of lipid-lowering regimens within the same population, using varying statins doses and/or potency, ezetimibe or PCSK9 inhibitors and compared the observed number of patients needed to be treated for 10 years to prevent one CVD event (NNT) with NNT predicted from trials of predominantly single-dose statin. Some 75439 participants in 10 randomized studies were included. The mean 10-year CVD risk in controls was around 50% and the incremental mean LDL cholesterol decrease 0.95 mmol/l (36.7 mg/dl). Observed NNT closely correlated with those predicted from predominantly single-dose statin trials [18.2 and 17.1; Pearson R=0.844 ( P =0.001)]. When pre-treatment LDL cholesterol exceeded 4 mmol/l (155 mg/dl), achieving a target LDL cholesterol of 1.8 mmol/l (70 mg/dl) was the most effective strategy. At lower pre-treatment levels, fixed-dose statin equivalent to atorvastatin 80 mg daily was superior. The target of 40% reduction in non-high density lipoprotein cholesterol was least effective regardless of pre-treatment LDL cholesterol. Summary: We conclude that when initial LDL cholesterol exceeds 4 mmol/l and absolute CVD risk demands it, a target value of 1.8 mmol/l should be achieved, if necessary by adding ezetimibe and/or PCSK9 inhibitors to statin treatment.